1999
DOI: 10.1038/44183
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of actin-based motility of Listeria and Shigella using pure proteins

Abstract: Actin polymerization is essential for cell locomotion and is thought to generate the force responsible for cellular protrusions. The Arp2/3 complex is required to stimulate actin assembly at the leading edge in response to signalling. The bacteria Listeria and Shigella bypass the signalling pathway and harness the Arp2/3 complex to induce actin assembly and to propel themselves in living cells. However, the Arp2/3 complex alone is insufficient to promote movement. Here we have used pure components of the actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

56
809
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 916 publications
(881 citation statements)
references
References 31 publications
56
809
1
3
Order By: Relevance
“…In the case of MDA-MB-231 cells, although we noticed a somewhat decrease in the overall flare of protrusion after Pfn1 depletion, polarised protrusion at the leading edge was still evident. It was previously implied that Pfn1 facilitates, but is not absolutely critical for the canonical WASP-Arp2/3-mediated, actinbased protrusions in migrating cells (Loisel et al, 1999). Since WASP-family proteins, Arp-2/3 as well as their upstream regulators (Rac1, Cdc42) are known to be overexpressed in several invasive cancers including breast cancer (Sahai, 2005), protrusion of tumour cells may be much less sensitive to loss of Pfn1 expression compared to vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of MDA-MB-231 cells, although we noticed a somewhat decrease in the overall flare of protrusion after Pfn1 depletion, polarised protrusion at the leading edge was still evident. It was previously implied that Pfn1 facilitates, but is not absolutely critical for the canonical WASP-Arp2/3-mediated, actinbased protrusions in migrating cells (Loisel et al, 1999). Since WASP-family proteins, Arp-2/3 as well as their upstream regulators (Rac1, Cdc42) are known to be overexpressed in several invasive cancers including breast cancer (Sahai, 2005), protrusion of tumour cells may be much less sensitive to loss of Pfn1 expression compared to vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mogilner and Oster showed that short stiff filaments are favorable for the elastic Brownian ratchet. Loisel et al (10) also showed that cofilin is required for robust comet tails. Cofilin promotes the turnover of the filaments so comet tails maintain a constant length as the bacterium moves forward.…”
Section: Mogilner and Oster 1996: Elastic Brownian Ratchet Mechanismmentioning
confidence: 97%
“…Selective pressures during evolution of the system~1 billion years ago arrived at the physically optimal angle of the branches. Reconstitution experiments (10) showed that movement of bacteria by actin comets depends on capping the filaments so their lengths are limited. Mogilner and Oster showed that short stiff filaments are favorable for the elastic Brownian ratchet.…”
Section: Mogilner and Oster 1996: Elastic Brownian Ratchet Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Actin comets can be reconstituted in vitro with five proteins and N-WASP-, or Listeria protein ActA-coated plastic beads [Cameron et al, 1999;Loisel et al, 1999;Pantaloni et al, 2001;Suetsugu et al, 2001c]. The five proteins are ADF/cofilin, profilin, Arp2/3 complex, barbed-end capping protein, and actin (Fig.…”
Section: Simplified Model Of Actin Cytoskeleton Reorganization: Actinmentioning
confidence: 99%